2004
DOI: 10.1197/j.aem.2003.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Needle Thoracostomy: Implications of Computed Tomography Chest Wall Thickness

Abstract: In this study, a catheter length of 5 cm would reliably penetrate the pleural space of only 75% of patients. A longer catheter should be considered, especially in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…One study sampling male American military personnel [15] reported that as age increased, CWT increased, though the age range was limited to 19-48 years. Several studies reported thicker chest walls in females, [14,16,19,21] and one of them noted that females exhibit a wider range of thicknesses than males.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study sampling male American military personnel [15] reported that as age increased, CWT increased, though the age range was limited to 19-48 years. Several studies reported thicker chest walls in females, [14,16,19,21] and one of them noted that females exhibit a wider range of thicknesses than males.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] In the 9 studies, there were a total of 1 504 participants. The reported CWT for adults at the 2nd intercostal space, mid clavicular line varied between 1.3 cm and 9.3 cm.…”
Section: Partmentioning
confidence: 99%
See 1 more Smart Citation
“…As the war progressed, the length of the needle used for decompression was increased as we learned that the chest wall thickness of military members was enough to make standard needle decompression ineffective up to 75% of the time. [17][18][19] However, as blast injuries became more commonplace, the CCC WG began to rethink the use of needle decompression on the battlefield. The crux of the argument centred on 2 issues: first, that tension pneumothoraces were less frequently noted in casualties, likely because of the advanced personal protective equipment that CF members were wearing 8,9 and, second, that providers continued to landmark incorrectly when performing needle decompression, risking injury to the heart and great vessels.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…The procedure is not benign, but, in the setting of tension pneumothorax, it is lifesaving. Dr. Biffl references a case report by Butler et al 1 in which a patient suffered a pulmonary artery laceration secondary to a needle thoracostomy. This procedure was performed on a patient who had decreased breath sounds and desaturation after endotracheal intubation, but there was no tension physiology otherwise present.…”
mentioning
confidence: 99%